Terminologically of Tasawuf : An Introduction - Azami, Yasin Syafii; Nurhuda, Abid; Murjazin, Murjazin (Advances in Humanities and Contemporary Studies, 2023)
Sufism is often considered old-fashioned and not open to change, even though tasawuf also accepts new things so that reforms occur both in etymology and terminology. And the purpose of this study is to describe the essence of Sufism in terminology. The method used is qualitative with literature study techniques, then all relevant data is collected, analyzed, and finally concluded the relevant content. The results of the study show that the essence of Sufism in terms of definition depends on the point of view of each person. The principles used are the Qur'an and Assunnah and include a special dimension to discuss how best to get closer to God so that the Divine appears, Ilahi Anta Maqsudi wa ridhaka mathlubi.